Kajian Pengembangan Produks Makanan Olahan Mangrove - Choliq Sabana (Jurnal Ekonomi Dan Bisnis, 2015)
Mangroves in addition to conservation of nature , mangroves can also be used as a basic ingredient of processedfoods . Mangrove has been shown to have content that is useful for the growth , development , and intelligence .There have been many people, especially coastal communities have made use of mangrove fruit as raw materialprocessed foods , such as syrups and other food . However, for people in Pekalongan not commonly utilizemangrove fruit  as raw material processed foods , it is because of the difficulty of raw materials . The results ofthe feasibility analysis shows that enterprises with raw materials processed foods such as  “Jenang Dodol” dan“Sirup Mangrove” is feasible by households and industry can be produced in a sustainable manner with thesupport of the raw material .